The Seniors - Aimufia, Glory (Evans Brothers (Nigeria Publishers) Ltd, 2009)
Ijeoma looks forward to life in Secondary school with great excitement. However, the stories she had heard about how seniors treat junior haunt her. Is her first day experience in secondary school a confirmation of these stories?...
Keywords: Juvenile Fiction / Adventure